Peran Pelaku Usaha Dalam Tata Kelola Kampung Wisata Kuliner Di Kelurahan Ledok, Kecamatan Argomulyo Kota Salatiga - Samtono Samtono; Andhi Supriyadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This service aims to develop a culinary tourism village based on local wisdom with a focus on cassava raw materials in Ledok Village, Salatiga City. This research involves local culinary business actors, local governments, and academics to improve skills, business governance, and promotion of cassava-based culinary products. The results of this service include improving the skills of culinary business actors, developing a diverse culinary menu, strengthening collaboration between various parties, as well as creating a management guide for culinary tourism villages. Evaluation of research results shows positive potential in increasing business actors' income, local tourism growth and village economic development. In conclusion, the development of a culinary tourism village based on local wisdom made from cassava has great potential to improve the quality of life of local communities and support the economic and tourism growth of Salatiga City. Collaboration and training are the keys to success in optimizing the potential of this culinary tourism.